Prevalence of Malnutrition in Bhal Region of Gujarat State - Gayatree Jadeja and M. S. Jakasaniya, (Indian Journal of Extension Education, 2017)
There has been increasing evidence that development of underweight and obesity has deleterious social and healthconsequences. The study was conducted to determine the prevalence of underweight and obesity in rural areas of Bhalregion of Gujarat state. Total of 1213 subjects of four different age groups were selected from different 80 villages of ruralarea. The height, weight were measured for all age groups. Mid upper arm circumference, hair colour and skin texturewere observed for preschool children as well as the blood pressure was measured for adults above 40 years. All parameterswere correlated with the body mass index. The results found were alarming. Majority of girls had malnourishmentsymptoms compared to boys. More of tobacco addiction was found in adult male and 40 to 49 years adults were sufferingfrom high blood pressure problem. Illiteracy was higher in female which is indirectly responsible for the health of thecommunity